Influence of previous acid etching on bond strength of universal adhesives to enamel and dentin - Torres, Carlos Rocha Gomes [UNESP]; Zanatta, Rayssa Ferreira [UNESP]; Da Silva, Tatiane Josefa [UNESP]; Huhtala, Maria Filomena Rocha Lima [UNESP]; Borges, Alessandra Bühler [UNESP] (My University, 2017)
The objective of this study was to evaluate the effect of acid pretreatment on the bond strength of composite resin bonded to enamel and dentin with 2 different universal self-etching adhesives. The null hypothesis was that the acid treatment performed prior to adhesive application would not significantly change the bond strength to enamel or dentin for either universal adhesive tested. A sample of 112 bovine incisors were selected and embedded in acrylic resin. Half were ground until a flat enamel surface was obtained, and the other half were polished until a 6 × 6-mm area of dentin was exposed, resulting into 2 groups (n = 56). The enamel and dentin groups were divided into 2 subgroups according to the adhesive system applied: Futurabond U or Scotchbond Universal. Each of these subgroups was divided into 2 additional subgroups (n = 14); 1 subgroup received phosphoric acid pretreatment, and 1 subgroup did not. The bond strength was assessed with a microtensile test. Data from enamel and dentin specimens were analyzed separately using 1-way analysis of variance. The acid pretreatment did not significantly change the bond strength of the adhesives tested, either to enamel (P = 0.4161) or to dentin (P = 0.4857). The acid etching pretreatment did not affect the bond strength to dentin and enamel when the tested universal multipurpose adhesive systems were used.
Keywords: Bond strength; Etch-and-rinse adhesive; Phosphoric acid; Self-etching adhesive; Universal adhesive